The Culturally-Anchored Entrepreneurship: The Mediating Role of Kasundaan Values in Driving Business Behavior in West Java - Nugraha, Yus (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: Entrepreneurship is not a cultural vacuum; it is deeply embedded in the social values of the community. This study challenges Western-centric models by examining how Kasundaan (Sundanese) values drive entrepreneurial behavior among 417 business owners in West Java, Indonesia. Utilizing Path Analysis, we investigate a complex mediation framework involving entrepreneurial intention, self-efficacy, and orientation. Our findings reveal that Kasundaan values act as a powerful cognitive driver, with the most profound impact observed on Entrepreneurial Orientation. This suggests that Sundanese cultural philosophy provides a robust strategic compass for risk-taking and proactiveness. Interestingly, the mediation through self-efficacy was the weakest, indicating that these cultural values influence strategic vision more than individual task-specific confidence. This research establishes a roadmap for "ethno-entrepreneurship" and provides empirical evidence for policy-makers to develop culture-based business interventions that leverage local wisdom to foster sustainable regional economic growth. Key words : Entrepreneurial Self-Efficacy, Entrepreneurial Intention, Entrepreneurial Orientation, Sundanese Value System, Entrepreneurial Behavior